163 AN AUDIT OF STAFF NAME BADGE VISIBILITY ON A STROKE UNIT IN A LARGE TEACHING HOSPITAL IN IRELAND. (25th October 2022) - Ryan, K; Healy, L; Crowley, P; Aherne, D; O'Donnell, M; Murphy, J
Abstract: Background: The National Patient Experience Survey highlighted the importance of name badge wearing in hospitals, with patients noting that badges made it easier to remember staff and refer to them by name. Based on her experience of identification, the #hellomynameis campaign was initiated in 2013 by Dr. Kate Granger to reinforce the importance of name badge wearing. In an era where mask wearing further inhibits communication and identification, clear identification has never been as important. This audit aims to assess the adherence to name badge wearing on a stroke unit. Methods: An observational audit was carried out in March 2022 over one morning. Staff were not notified in advance of the audit. Inclusion criteria: Name badge placed on uniform in a visible place with/without photo. Exclusion criteria: Lanyards with swipe card identification due to small font and difficulty in viewing name and photo. The standard for this audit was for 100% compliance with name badge wearing as name badges are a crucial element of communication in best patient care. Results: 24 people across 11 different professions were identified on the ward. Seven staff members (29.16%) were wearing name badges of which 5 included photos therefore the standard set for this audit was not met. Conclusion: There was an overall poor compliance with name badge wearing on the stroke ward. Compliance varied amongst the different professions with Speech and Language therapists, Occupational Therapists and nursing staff having a higher compliance with wearing name badges compared to other professions. Most staff members had identification in the form of swipe cards on lanyards, but did not wear clearly legible name badges. Education around the importance of name badges and distribution of name badges to all staff members is planned prior to a re-audit phase.